Phyto-toxic Effect of Heavy Metal (CdCl2) on Seed Germination, Seedling Growth and Antioxidant Defence Metabolism in Wheat (Triticum aestivum L.) Variety HUW-234 - Siddique, Anaytullah; Dubey, Anand Prakash (International Journal of Bio-resource and Stress Management, 2017)
The experiments were conducted to assess the phytotoxic effect of heavy metal (CdCl2). The responses of treatment effect comprises the variables germination %, length (cm), fresh weight and dry weight (mg) of shoot and root, root/shoot ratio, seed vigour index (SVI), reducing sugar, non reducing sugar, total sugar (mg g-1), chlorophyll content (mg g-1), cadmium uptake (ppm g-1), proline content (µg g-1), relative water content (RWC%) and superoxide dismutase (SOD, unit×102 g-1 f. weight min-1). CdCl2 treated sets showed reduction in percent of seed germination, length (cm), fresh weight and dry weight (mg) of shoot and root, root/shoot ratio, seed vigour index (SVI) with increasing the concentrations of CdCl2 in comparison to control set. A reduction in breakdown of reducing sugar to non reducing sugar and total sugar is correlated with decline of amylase activity along with increasing the concentrations of CdCl2 in comparison to control one. The chlorophyll content was found in decreasing trend with increasing the concentrations of CdCl2 in comparison to control. However, the uptake of cadmium was increased with increasing the concentrations up to 100 ppm CdCl2. The proline content and superoxide Dismutase (SOD) was found to be high in higher concentrations of CdCl2 treated set and while the enhancement was started since initial concentration CdCl2 (i.e., 25 ppm). However, the least amount was recorded in control set. On the contrary, RWC% was found to be reduced with increasing the concentrations of CdCl2 up to 100 ppm even though the maximum RWC% was measured in control set.